Beyond Categories: Power, Recognition and the Conditions for Equity - Moncrieffe, Joy M. (World Bank, 2012)
Poverty and the development of inter-group inequalities in Uganda, with particular reference to ethnic communities and women, are studied. This paper contends that assets and opportunities alone are unlikely to solve inequality. Using the Batwa people and women in Uganda as examples, it shows that equity requires deep understanding and real knowledge of the groups, subgroups and individuals that policy-makers aim to support. It is also critical to understand the institutional arrangements, policy responses and social and political alliances that support reformist collective action and political agency that hold inequality in place.